Новые подходы к комплексной токсиколого-гигиенической оценке безопасности кабельной продукции = New approaches to integrated toxicological and hygienic safety assessment of cables products - Tretyakova, E. V. (Journal of Education, Health and Sport, 2015)
Tretyakova E. V. Новые подходы к комплексной токсиколого-гигиенической оценке безопасности кабельной продукции = New approaches to integrated toxicological and hygienic safety assessment of cables products. Journal of Education, Health and Sport. 2015;5(4):157-168. ISSN 2391-8306. DOI: 10.5281/zenodo.16696 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A157-168 https://pbn.nauka.gov.pl/works/553789 http://dx.doi.org/ 10.5281/zenodo.16696 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2015. Revised 27.03.2015. Accepted: 27.03.2015. НОВЫЕ ПОДХОДЫ К КОМПЛЕКСНОЙ ТОКСИКОЛОГО-ГИГИЕНИЧЕСКОЙ ОЦЕНКЕ БЕЗОПАСНОСТИ КАБЕЛЬНОЙ ПРОДУКЦИИ New approaches to integrated toxicological and hygienic safety assessment of cables products Е.В. Третьякова E.V. Tretyakova Украинский научно-исследовательский институт медицины транспорта Минздрава Украины State Enterprise Ukrainian scientific-research institute of transport medicine, Ministry of Pablic Health of Ukraine Abstract The article highlights the problem of cable products safety and imperfect criterion and methodological bases of conducting small-scale tests of combustion products toxicity. The high level of fire danger of such products is associated with its combustible components, mainly polymeric materials, as well as the specifics of cable products maintenance. It is shown that the conducting of standard tests for each component separately and further application of computational methods for the cable assembly, leads to unlawful referral to a class of products more dangerous than it actually belongs in 60% of cases. The last one, as a result, significantly restricts the scope of the many types of cables on formal grounds laid down in the relevant regulations. The rational approach includes a three-step test, which forms an adequate model, that reflects the realities of burning cables. The protocol also involves additional studies, particularly determination of heavy metals and assessing the contribution of the aerosol phase in the combustion products toxicity. All made recommendations will help to more effective solve the problem of cable products safety for human health. Keywords: cable production, the toxicity of combustion products, polymeric materials, fire safety, certification tests. Реферат В статье освещается проблема безопасности применения кабельной продукции и несовершенство критериально-методической базы, регламентирующей проведение маломасштабных испытаний токсичности продуктов горения. Высокий уровень пожарной опасности данного вида продукции связан с использованием в ее составе горючих, главным образом, полимерных материалов, а также со спецификой эксплуатации изделий. Показано, что при проведении стандартных испытаний, включающих исследование по каждому компоненту отдельно, а затем применение расчетных методов для кабеля в сборке, неправомерно относит более 60,0 % изделий к классу более опасных. Последнее, как следствие, значительно ограничивает область применения многих типов КП по формальному признаку, заложенному в действующих нормативных документах. Предложен рациональный подход трехэтапных испытаний, адекватная модель, отражающая реальные условия горения кабельной продукции, а также проведение дополнительных исследований, включающих определение тяжелых металлов и оценку вклада аэрозольной фазы в токсичность продуктов горения, что позволит в комплексе решить проблему безопасности применения данного вида продукции для здоровья человека. Ключевые слова: кабельная продукция, токсичность продуктов горения, полимерные материалы, пожарная безопасность, сертификационные испытания.